Penerapan Metode Certainty Factor dan Dempster Shafer dalam Sistem Pakar Penerima Bantuan Daerah pada Jorong Koto Tuo - Hezy Kurnia; Devia Kartika (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2023)
The issue of poverty is a classic humanitarian problem and a solution needs to be found. In Indonesia, the causes of poverty itself are also diverse, including an inadequate minimum wage, a large number of family members and increased unemployment due to the difficulty in finding jobs. Not only in urban areas, the problem of poverty is even more so in regions or villages. Therefore, an integrated effort is needed to overcome this problem. As an effort to accelerate poverty reduction, since 2017 the government has implemented the Family Hope Program (PKH). In order to be right on target in distributing aid, an expert system was designed to determine the recipients of this regional assistance. With the existence of an expert system for determining regional aid recipients for poor families in the Family Hope Program (PKH), it will improve services for poor families to have access and make good use of social services such as health, education, food and nutrition, care, assistance, and various other social protection programs. This research was also conducted to minimize misunderstandings that occurred in the community in deciding the criteria for receiving regional assistance according to the conditions of the recipient. Then the results of the analysis are applied in an application design that is able to make decisions consistently, quickly, precisely and has the percentage needed in making the final decision using the Visual Basic programming language and the MySQL database